The Influence of Profit Management, Transfer Pricing, and Capital Intensity on Tax Avoidance with Company Size as a Moderation Variable - Fitriani, Riri; Taqi, Muhamad (Islamic Economics Methodology, 2024)
This research aims to determine the effect of earnings management, transfer pricing, and capital intensity on tax avoidance with company size as a moderating variable. The research objects used in this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2023. This research is a type of quantitative research with multiple linear regression models and Moderated Regression Analysis (MRA). In selecting samples that met the criteria, 30 companies were obtained. This research uses secondary data based on manufacturing company financial reports obtained from the Indonesia Stock Exchange website and related company websites. Data processing was carried out using the SPSS 25 application program. Partial research results showed that earnings management had an effect on tax avoidance, transfer pricing had an effect on tax avoidance, capital intensity had no effect on tax avoidance while moderated regression analysis (MRA) testing showed that company size moderated the effect of earnings management on tax avoidance, company size cannot moderate the effect of transfer pricing on tax avoidance, and company size cannot moderate the effect of capital intensity on tax avoidance.